PEMBUATAN DAN UJI MUTU FISIK SEDIAAN BALSAM STIK EKSTRAK DAUN KEMANGI (Ocimum basilicum L.) - taufiq, taufiq; Astia Putri (Jurnal Kesehatan Yamasi Makassar, 2024)
Balsam stick is an innovative alternative preparation of balsam preparations to increase user comfort and ease of use. The aim of this research was to determine whether basil leaves (Ocimum basilicum L.) could be formulated in the form of stick balm. This research uses experimental research methods. By using various concentration variants starting from 1%, 3% and 5% formulations using several evaluation tests for balm preparations including organoleptic tests, homogeneity tests, pH tests, spreadability tests and adhesion tests. The research results obtained for the organoleptic test in the form of pH showed that the pH test results produced a pH of 6 and were homogeneous for each concentration. In the organoleptic test, it has a semi-solid form, has a distinctive aroma of basil leaves and has a light green color at a concentration of 1% and a dark green color at a concentration of 3% and 5%. In the spreadability test, a concentration of 1% produced 5.4 cm, a concentration of 3% produced 6.1 cm and a concentration of 5% produced 5.6 cm. In the adhesion test at a concentration of 1%, adhesion was obtained for 12 seconds, at a concentration of 3% for 17 seconds, and at a concentration of 5%, adhesion was obtained for 7 seconds.